Pengembangan Media Belajar Fisika Mandiri Berbasis Aplikasi Smartphone pada Materi Suhu dan Kalor - Wijaya, Anthony; Pratidhina, Elisabeth; Herwinarso, Herwinarso; Untung, Budijanto (Ideas Publishing, 2024)
In physics learning, learning media are needed that can present visualizations of physics concepts and their applications so that they are easily understood by students. This study aims to: (1) develop learning media in the form of smartphone applications to facilitate students in learning physics on the topic of temperature and heat, (2) determine the quality of the media developed, (3) determine user responses to the media developed. This study uses a development research method with the ADDIE framework consisting of the stages of analyze, design, develop, implement, and evaluate. The application contains several menus including introduction, material, and quizzes. Based on expert assessment, the media is very suitable for use, the average assessment score is 3.48 (out of a maximum value of 4.00). In the implementation, the application was tested on high school students online. A sample of 51 students were involved in the implementation stage. Student responses during implementation were very positive so that the application developed has the potential to be used as an independent learning medium.